1993
DOI: 10.5089/9781451849196.001
|View full text |Cite
|
Sign up to set email alerts
|

Economic Trends in Africa: The Economic Performance of Sub-Saharan African Countries

Abstract: This is a Working Paper and the author would welcome any comments on the present text Citations should refer to a Working Paper of the International Monetary Fund, mentioning the author, and the date of issuance. The views expressed are those of the author and do not necessarily represent those of the Fund.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Dhonte et al (1994) found that for many countries the spread between the official and parallel market rates was significantly lower in mid-1994 than it was at the end of 1990. Burundi and Nigeria were the main exceptions, where the spreads widened.…”
mentioning
confidence: 97%
“…Dhonte et al (1994) found that for many countries the spread between the official and parallel market rates was significantly lower in mid-1994 than it was at the end of 1990. Burundi and Nigeria were the main exceptions, where the spreads widened.…”
mentioning
confidence: 97%